Bloody nipple discharge in a 7-month-old boy - Zaid, Ahmed (BMJ Publishing Group, 2011)
Isolated bloody nipple discharge is rare in infancy and is usually idiopathic. Discharge commonly resolves spontaneously, and ultrasonography is a useful diagnostic technique to detect the cause of discharge. The authors report a 7-month-old boy who presented with unilateral spontaneous bloody nipple discharge for 1 month without signs of infection or mass.